PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI BERBASIS GAMBAR PADA MATERI SISTEM PENCERNAAN UNTUK SMA - Sari, Kumala; Ardi, Ardi; Risdawati, Renny (Pendidikan Biologi, 2013)
AbstractThis research is a development research, and his final outcome is a studentworksheet (LKS). LKS is a education media that contains of learning materials which  arranged  in a  systematic,  operasional  and  directed,  beside  it  that  also comes with the working step of pratikum. Students will be facilitated in understanding of biology material, by using student biology worksheets.  This research to generate image-based biology worksheets that can facilitate students in understanding the theory. This research has four stages, namely definition, design, development and dessiminate. Based on the result obtained, it can be concluded that the developed LKS had a valid and practical, therefore LKS can already be used at the time of learning.